Visible and invisible water transport components of the East European Plain and Trans-Urals in prehistory - Kashina, Ekaterina; Shutikhin, Aleksandr (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
In this paper we briefly discuss the direct and indirect evidence of the diverse watercraft in existence in the East European and the Trans-Ural forest zone since the Mesolithic until the Bronze Age. Two Bronze Age logboats have been investigated in Lithuania and Russia. The presence of skin and bark boats is hypothetically based on the unique find of a ceramic canoe sculpture from the Central Russia dated to the 3rd millennium BC. The group of lightweight, short wooden paddles and of the rare two-blade paddles gives us the indirect evidence of frame/bark boat extensive use since the Mesolithic Age.